Legalitas Surat Wasiat dalam Sistem Pewarisan: Analisis Antara Kompilasi Hukum Islam dan Hukum Perdata - Hazarul Aswat; Ilham Maulidin (Al Fuadiy Jurnal Hukum Keluarga Islam, 2026)
The distribution of inheritance is an important aspect of the legal system in Indonesia, influenced by Islamic law and Western civil law. Differences in the regulation of the legality of wills between the Compilation of Islamic Law (KHI) and the Civil Code (KUHPerdata) have led the state to strive for legal harmonization by providing dual legal frameworks for Muslim and non-Muslim communities. This study aims to conduct a comparative analysis of the legality of wills under these two legal systems. The method used is normative legal research employing statutory and comparative approaches, utilizing secondary data obtained through library research and document analysis. The results show that KHI limits wills to a maximum of one-third of the estate and emphasizes the protection of heirs, whereas the Civil Code grants broader freedom to the testator, with limitations imposed through the concept of legitime portie. Both systems share similarities in recognizing a will as a unilateral declaration of intent, requiring legal capacity, and allowing for revocation. However, they differ significantly in terms of the limitation of assets, the designation of beneficiaries, and the underlying legal protection paradigm. It can be concluded that the two systems are not contradictory but rather reflect different approaches that hold potential for harmonization. This research contributes by providing a comprehensive and systematic comparative analysis of the legality of wills to strengthen legal certainty and minimize inheritance disputes in Indonesia.